Trustworthy Parameter in Delayed Cholecystectomy using analytic hierarchy process (Eurasian Medical Research Periodical, 2022)
Delayed cholecystectomy after 6 weeks of onset of acute cholecystitis is regarded as a standard option by many surgeons during management of acute cholecystitis as those surgeons wait for subsiding of acute inflammation aiming for decreasing morbidity and mortality. There are some parameters that are can be dependable and have an importance when surgeons select delayed cholecystectomy as an preferred option. In this study the analytic hierarchy process is used to assess the optimum parameter that the surgeons can depended on it when choosing delayed cholecystectomy in cholecystitis cases. Consultant surgeons working at baqubah teaching hospital with good surgical expereince give data to this study and from these data the weights of all parameters are calculated